Effect of cereal rye cover crop termination timings on weed control and corn yield under a two-pass herbicide program - Godar, Amar S.; Norsworthy, Jason K.; Barber, L. Tom (Frontiers in Agronomy, 2024)
Cover crops, including cereal rye, are generally known to suppress weeds in various cropping systems; however, research on their effective use is lacking. This study investigated the effects of different cereal rye termination timings on weed control and corn performance in a two-pass herbicide program across 5 site-years (2021–2023) in Arkansas, USA. The herbicide program consisted of one application at cereal rye (Secale cereale) termination (cereal rye environment) or at corn (Zea mays) planting (conventional system) and another at the V4 corn stage. Palmer amaranth (Amaranthus palmeri) at V4 corn was better controlled in cereal rye environments regardless of its termination timing (>75%) than in the conventional corn system (<50%), and the control was generally excellent in both systems 4 weeks later, with subtly greater control in the cereal rye environments. In contrast, yellow nutsedge (Cyperus esculentus) control, in general, was slightly less in the cereal rye environments than in the conventional system. Barnyardgrass (Echinochloa crus–galli) and broadleaf signalgrass (Urochloa platyphylla) control was similar to that of Palmer amaranth, especially at the V4 corn stage, with clear benefits in its control with the later termination timings. Corn height was greater (by 8% to 10%) in cereal rye environments terminated at 1 or 2 weeks after corn planting compared to the conventional system or other cereal rye environments. Corn yield was similar between the conventional system and the cereal rye environments terminated before corn planting; however, the yield was 16% to 22% less with those terminated at or after corn planting. These findings indicate the constrained use of cereal rye in corn, with its termination time optimized for 2 weeks before corn planting. Further research could identify factors that mitigate the yield loss from delayed cereal rye termination and improve its use as a cover crop in corn.